The Influence of The Think Pair Share Model and Mind Mapping on Exposition Writing Skills in Terms of Student Learning Independence of Teuku Umar Cluster Students - Cahyono, Ady; Murtono, Murtono; Suad, Suad; Soltlikova, Rimajon (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2022)
Tujuan penelitian ini adalah 1) menjelaskan pengaruh model think pair share dan mind mapping terhadap pembelajaran menulis eksposisi ditinjau dari kemandirian belajar siswa, 2) Mengetahui perbedaan pengaruh model think pair share dan mind mapping dalam pembelajaran menulis karangan eksposisi ditinjau dari kemandirian belajar siswa. Penelitian ini merupakan jenis penelitian eksperimen dengan desain faktorial. Pengumpulan data melalui tes, observasi, wawancara, dan dokumentasi. Hasil analisis uji hipotesis disajikan sebagai berikut: 1) Hipotesis pertama menunjukkan bahwa nilai T-hitung keterampilan menulis eksposisi siswa adalah 2,122 dan tingkat signifikansi 0,039 (0,05) dan kemandirian belajar siswa adalah 2,068 dan Tingkat signifikansi 0,044 (0,05).; 2) Hipotesis kedua menunjukkan nilai T-hitung keterampilan menulis eksposisi sebesar 2,755 dan taraf signifikansi 0,036 (0,05) serta nilai t hitung kemandirian belajar siswa sebesar 2,256 dan taraf signifikansi 0,029 (0,05) .; 3) Hipotesis ketiga menunjukkan nilai sebesar 2,122 dengan tingkat signifikansi 0,039 (0,05) terhadap keterampilan menulis eksposisi dan hasil belajar siswa. Maka dapat disimpulkan bahwa adanya Pengaruh model think pair share dan mind mapping terhadap keterampilan menulis eksposisi ditinjau dari kemandirian belajar siswa. The objectives of this study are 1) to explain the influence of the think pair share and mind mapping model on learning to write exposition in terms of student learning independence, 2) Knowing the difference in the influence of the think pair share model  and mind mapping in learning to write exposition essays in terms of student learning independence. This research is a type of experimental factorial design research. Data collection through tests, observation, interviews, and documentation. The results of the hypothesis test analysis are presented as follows: 1) The first hypothesis shows that the T-count  value on students' exposition writing skills is 2.122 and the significance level is 0.039 (0.05) and the student learning independence is 2.068 and  The significance level of 0.044 (0.05).;  2) The second hypothesis shows that the T-count value of exposition writing skills is 2.755 and a significance level of 0.036 (0.05) and the Traume value of student learning independence is 2.256 and a significance level of 0.029 (0,  05).; 3) The third hypothesis shows that value of 2.122 with a significance level of 0.039 (0.05) on the exposition writing skills and the results of the students'   learning independence testing the tcount value was 2.127 with a significance level of 0.038 (0.05) indicating that there was a significant difference in the exposition writing skills and student learning independence with the think pair share learning model compared to mind mapping learning model so that the first hypothesis is accepted